Kearifan Lokal Sebagai Budaya Dan Inspirasi Penciptaan Tari karang Tumandang - Dara Adelia; Vito Widyatama (TAMUMATRA, 2024)
As one of the objectives to know and understand the creative process in the creation of a dance that becomes the identity of a region and as an effort to conserve the values of local wisdom. The author aims to examine the process of creating dance originating from an area, namely Karanganyar Regency, and what meaning it contains. In today's era, there are many young people who are indifferent to the cultures around them, but the effort to create the Tumandang Coral Dance is aimed at children until this teenager has succeeded in maintaining the existing history as a forum for cultural preservation. This dance is introduced in one way, namely the disdikbud held a Tumandag Coral Dance competition through a festival, at the annual event commemorating the anniversary of Karanganyar Regency, with this art makes children to teenagers understand the history contained in the region, and also enthusiastic to get to know more about the arts and culture in the region.